Woolly mammoth and Man at Krasnoyarskaya Kurya site, West Siberian Plain, Russia (excavation results of 2014) - Seuru Samuel; Leshchinskiy Sergey; Auguste Patrick; Fedyaev Nikita (BSGF - Earth Sciences Bulletin, 2017)
Detailed paleobiological and taphonomic analyses were carried out on the bone accumulations discovered during the 2014 excavations at the Krasnoyarskaya Kurya site, southeastern part of western Siberia (Russia). The fossiliferous site contains three bone-bearing horizons. Mammal remains are rare in the upper level and they were not found during the 2014 excavation. The middle and lower levels yielded exclusively remains of the woolly mammoth, Mammuthus primigenius. The middle level (stratigraphic layer 5) is a result of an in situ accumulation in alluvial sediments. At least three individuals are identified: a juvenile (< 6-10 years old in AEY) of 1.8 m shoulder height and weighing 1 ton; a young adult (ca. 24 years old in AEY) and an old mammoth (> 43 years old in AEY) of 2.9 m of shoulder height and 3.8 t. Their remains were buried in conditions similar to those of a floodplain scroll/natural levee or an islet. Bones stayed on the subsurface for a long time, allowing thus carnivores to reach them easily. The lower level (stratigraphic layer 6) is composed of at least four animals: two juveniles (< 6-10 years old in AEY) and two adults (> 11-13 years old in AEY). The material only enables to determine that one juvenile is 1.5 m at shoulder height and weighs ca. 610 kg, while a young adult should have a body mass of ca. 1,600 kg. No human artefacts or any cut-marks on bones were found in either of these two levels during the 2014 excavation. However, the excavations carried out during the years 2007 to 2010 had allowed the discovery of Palaeolithic artefacts in the lower level, which was formed in alluvial-lacustrine conditions. This indicates that humans had visited this a priori in situ mammoth assemblage. It is likely that at the beginning of spring, the oxbow lake had trapped woolly mammoths. Humans and carnivores had then sorted out and taken away any useful remains. Radiocarbon dating indicates that the mammoth died at the early phase of the Last Glacial Maximum, at about 14C – 20 000 BP (~ 24 000 years cal BP). Isotopic analyses of the collagen from the mammoth remains argue that the animal was living at the time in a steppe landscape, which was dominated by grass-like vegetation.